IMPACT OF SOCIAL INTELLIGENCE ON PROFESSIONAL PERFORMANCE - Sergeeva, Marina; Lukashenko, Dmitry; Suslov, Yuri; Fedorov, Alexander; Shaleeva, Elena (Revista Inclusiones, 2020)
In contemporary society we observe rapid growth in the volume, density and complexity of communications, due to the key trends in the development of information technologies and their impact on society. In this regard, the importance of social and communication abilities, skills and knowledge associated with social interactions is significantly increasing. This process dictates the need for their development both within the educational system and beyond. In this context, the social intelligence as a fundamentally important parameter for the development of social interaction abilities and understanding in the social sphere is especially important. Analysis of modern studies in the field of social intelligence, the content and definition of this concept and the features of its development allow us to conclude that it is the most optimal way to develop social intelligence in the framework of language education in higher educational institutions. Social intelligence is an integrative concept and includes a wide variety of abilities, knowledge and skills. The importance and necessity of their development is not in doubt among psychologists and educators. Researchers offer various models for the structure of social intelligence and argue about the components of this concept.